Structural equation modeling in the acceptance of internet banking in the city of Split - Marija Vuković; Snježana Pivac; Duje Kundid (Croatian Operational Research Review, 2019)
Electronic banking and electronic commerce have lately become an inevitable aspect of financial services. According to data about the percentage of users of Internet banking in Europe, Croatia is at the bottom of the list, with a low number of users. Thus, the question of the acceptance and use of this kind of technology arises. This research uses structural equation modeling to explore whether the motivation for the acceptance and use of Internet banking can be explained by the technology acceptance model (TAM) in the city of Split, Croatia. TAM explains the intent of using information systems through the perceived ease of use and the perceived usefulness of a system. It consists of multiple causal relationships, so structural equation modeling is adequate for hypothesis testing. A survey analysis was designed and applied on a sample of 282 working residents of Split. To make the results more credible, the gender and age structure of the sample was harmonized with the population. It is concluded that both elements of TAM positively influence the acceptance of Internet banking in Split. Since there is not much research on the use of Internet banking in Croatia and Southeast Europe, this research contributes to the poor amount of literature in this scientific area for these countries. The research findings can also help banks to understand the factors of Internet banking acceptance and to develop expansion strategies. Future research could include a cross-country comparison of individuals’ perception about Internet banking, as well as the dependence relationships of TAM factors.